The Interaction Strength, Frequency-shifts and Covalence of the C2H4O∙∙∙HOCl and C2H5N∙∙∙HOCl Heterocyclic Complexes - de Oliveira, Boaz Galdino (Orbital: The Electronic Journal of Chemistry, 2017)
A theoretical study of the structural parameters, electronic properties and vibration modes of the C2H4O∙∙∙HOCl and C2H5N∙∙∙HOCl complexes. The great particularity of these complexes is the O–Cl s-hole, which is considered a proton donor center due to the depletion of charge density along the bonding axis. The examination of the interaction strength complexes was conducted through the intermolecular length, interaction energy and charge transference. The red shifts in the stretch frequencies of the H–O and O–Cl bonds as well as the identification of the new vibration modes were also presented. Regarding the hybrid orbitals, the contributions of the s and p orbitals were used to value the red shifts in the H–O and O–Cl bonds. The covalence of the O∙∙∙H and N∙∙∙H hydrogen bonds was also examined. DOI: http://dx.doi.org/10.17807/orbital.v9i2.853